Re-mediation and remedies: positioning ecological art of the 21st century in the quest for biodiverse future (Itinera, 2025)
The paper addresses the development of ecological art or Eco Art movements since the inception of the new millennium, focussing on the re-mediation of artistic practices towards sustainable futures and the emerging remedies in the quest for biodiversity consciousness. Starting with an analysis of engagement as a peculiar legacy of the 20th century Avant-Gardes, the paper discusses the shift in the 21st century with regard to the environmental awareness of artists engaged in sustainability. The paper argues that practitioners and practices have evolved in a twofold direction: on the one side towards a manifest way of positioning themselves in relation to sustainability issues, while on the other side exploring a set of postmodernist devices as societal remedies in the frame of biodiversity topics.
Keywords: Eco Art; Public Art; manifesto; sustainability; engagement